Radio Programme on how to overcome Banana Weevils on your Farm. - Mubiru, Wasswa (Technical Centre for Agricultural and Rural Cooperation, 2008)
Banana is a very important crop not only in Uganda, but all over the world. It is the world's fourth most widely-grown food crop after rice, wheat and maize, and the most important food staple in many other countries in Africa. In recent years, banana productivity in Uganda has been decreasing due to pests and diseases, declining soil fertility and socio-economic factors such as inadequate labour and marketing problems. Most banana workers in Africa are women, a trend which may be increasing due to migration of males in search of work. It is important that women especially listen carefully to this radio programme.